Implementation evaluation of academic detailing on naloxone prescribing trends at the United States Veterans Health Administration. (17th July 2019) - Bounthavong, Mark; Devine, Emily Beth; Christopher, Melissa L. D.; Harvey, Michael A.; Veenstra, David L.; Basu, Anirban
Abstract: Objective: Academic detailing in partnership with the Opioid Overdose Education and Naloxone Distribution (OEND) program was implemented to increase naloxone access for the prevention of opioid overdose mortality in veterans at the U.S. Department of Veterans Affairs (VA). However, implementation was not uniform leading to varying levels of intervention exposure potentially impacting naloxone prescribing. We examined the impact of implementation strength (proportion of providers exposed to academic detailing) at each station on naloxone prescribing from September 2014 to December 2017. Study Design and Setting: Retrospective cohort design with fixed effects models at the VA. Data Collection/Extraction Methods: We used VA Corporate Data Warehouse for data on pharmacy dispensing, station‐, provider‐ and patient‐level characteristics. OEND‐specific academic detailing activities came from data recorded by academic detailers using Salesforce.com. Principal Findings: VA stations wherein 100 percent of providers exposed to an OEND‐related academic detailing educational outreach visit experienced an increased incident rate of naloxone prescribing that was 5.52 times the incident rate of stations where no providers were exposed; alternatively, this is equivalent to an average monthly increase of 2.60 naloxone prescriptions per 1000 population at risk for opioid overdose. Conclusions: Our findings highlight the importance of academic detailing's implementation strength on naloxone prescribing. Decision makers must carefully consider the implementation process to achieve the greatest effectiveness from the intervention.